Grain yield, biomass productivity and water use efficiency in quinoa (Chenopodium quinoa Willd.) under drought stress - Telahigue, Dalel Chakri; Yahia, Laila Ben; Aljane, Fateh; Belhouchett, Khaled; Toumi, Lamjed (Journal of Scientific Agriculture, 2017)
Five quinoa cultivars introduced from Egypte DRC (Desert Research Center-Caire) were tested in an experimental station in Tunisia located under arid climatic conditions. In order to test their adaptation to abiotic constraints; water requirements, yield (grain, dry matter) and water use efficiency (WUE) were correlated to three water stress: T100% of field capacity (T1), T60% of field capacity (T2) and T30% of field capacity (T3). Net irrigation water requirement was estimated using CROPWAT 8.0 software. The study aims to develop an irrigation scheduling for quinoa from January to Jun during 2015 season. The ET0 was between 1.08 mm/day and 4.95 mm/day and net irrigation water requirement was 287.2 mm. For grain yield, 1000 grains weight and dry matter production results show significant differences between cultivars and water stress. The seeds productivity of the five cultivars ranges between 2092.6kg/ha and 270kg/ha under full irrigation and it decreases to reach up 74% under T3 of field capacity stress in comparison with control stress. Similar results were shown for dry matter production. On refilling soil to field capacity with irrigation at critical depletion, 70% field efficiency was achieved which correspond to optimal condition, while adapting fixed interval per stage. For WUE, highest value of irrigation and total water use efficiency for both grain and dry matter ??were recorded to the T2 hydrous stress.